Inflammatory bowel disease and mycobacteria: how much can we trust isoniazid prophylaxis during antitumor necrosis factor therapy?. Issue 7 (July 2019) - Akyuz, Filiz; Cavus, Bilger; Iliaz, Raim; Soyer, Ozlem M.; Ormeci, Asli; Evirgen, Sami; Onder, Semen; Koksalan, Kaya; Keskin, Metin; Karaca, Cetin; Demir, Kadir; Gulluoglu, Mine; et al.
Abstract : Objectives: Isoniazid (INH) prophylaxis is recommended for the prevention of tuberculosis (TB) reactivation before or/and during initiation of treatment with tumour necrosis factor antagonists (anti-TNF agents). Nonetheless, the long-term effectiveness of chemoprophylaxis is not clear. In this study, we aimed to evaluate the characteristics of patients who developed TB reactivation in spite of INH prophylaxis associated with anti-TNF treatment. Patients and methods: In this retrospective study, medical records of 1263 patients with inflammatory bowel disease were reviewed. Baseline TB screening tests (purified protein derivative test and/or QuantiFERON-TB Gold test) were performed on all patients before initiation of anti-TNF therapy. Patients with purified protein derivative of more than 5 mm and/or a positive result of the QuantiFERON-TB Gold test received INH prophylaxis for 9 months. We analysed the data of patients diagnosed with TB reactivation during the anti-TNF treatment despite INH chemoprophylaxis. Results: Overall, 175 patients underwent anti-TNF treatment. Sixty of these 175 patients had pretreatment testing showing latent TB infection and therefore were treated concomitantly with INH for 9 months in addition to their anti-TNF treatment. TB reactivation occurred in four of these 60 co-INH/anti-TNF treated patients. Active TB was diagnosed after 37.5±27 (range: 18–84) months of anti-TNF treatment. In two of the four patients that active TB was diagnosed, was also detected other Mycobacterium spp.: M. bovis in one patient and M. genavense in the other one. Conclusion: INH chemoprophylaxis may not prevent the reactivation of TB during anti-TNF therapy in the long-term. Patients should be carefully and periodically screened for TB reactivation during anti-TNF therapy.